Analisis Penggunaan Bahasa Gaul dan Dampaknya Terhadap Keterampilan Berbahasa Indonesia di Kalangan Mahasiswa Prodi Kewirausahaan Universitas Negeri Medan: Penelitian - Adisty Yulia Rangkuti; Diki Maulana Ramadhan; Dziban Ali Ashab; Firza Aditya Ramadhan; Tiara Fadillah; Nurul Azizah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The development of technology and social media has influenced the way teenagers, especially university students, communicate through the use of slang. This study aims to analyze the use of slang and its impact on Indonesian language proficiency among students of the Entrepreneurship Study Program at Universitas Negeri Medan. This research employs a descriptive approach with a qualitative method. Data were collected through questionnaire distributed to 60 active social media users and supplemented with brief interviews. Data analysis was conducted descriptively using the Miles & Huberman model. The results indicate that slang has become an important part of students’ daily interactions, particularly on social media platforms such as Instagram and TikTok, and functions as a social identity that enhances closeness among peers. However, excessive use of slang may negatively affect formal Indonesian language skills, such as difficulties in maintaining consistency in using standard language and recognizing formal vocabulary. This study shows that students need to balance the use of slang and formal language to maintain their Indonesian language proficiency, particularly in academic and professional contexts.